Pengaruh Kepuasan Kerja, Stres Kerja, Dan Lingkungan Kerja Terhadap Turnover Intention Karyawan Pada PT Indoaluminium Intikarsa Industri Di Cikarang - Mega Rahmanda Zulhidayani; Bayu Seno Pitoyo; Dewi Sri Wulandari (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This research aims to determine whether there is an influence on job satisfaction, work stress and work environment on turnover intention. The research carried out is quantitative research. The data source used was primary data which was carried out through a questionnaire processed using SPSS 26.0 and the total sample in this study was 61 respondents. The results of the regression show that partially there is no significant effect between job satisfaction and employee turnover intention at PT Indoalumnium Intikarsa Industri, there is a partial significant effect between work stress and employee turnover intention at PT Indoalumnium Intikarsa Industri, the work environment partially has no significant effect on turnover employee intention at PT Indoalumnium Intikarsa Industri. Job satisfaction, work stress and work environment simultaneously have a significant effect on employee turnover intention at PT Indoalumnium Intikarsa Industri.